Propuesta para la implementación del procedimiento especial para contravenciones en violencia intrafamiliar - Urgilés García, María Dolores (2011)
Domestic violence is a common violation of human rights, although it has serious consequences in the societies and their individuals, it has not given the importance that it deserves. Notwithstanding, considerable efforts must be made according to finish this type of abuse. Thus, as human beings, rational and fundamental pillars of our society are called to assume a fervent commitment to fight for compliance with the legal principles enshrined in the Constitution, international conventions and other legal regulations. This thesis aims to find the weaknesses in domestic violence matters, deriving from the institutions and officials, the lack of or poor implementation of existing standards and finally analyze the sanctions, in order to obtain that the victimizers not only serve a sentence but can be rehabilitated and efficient for society. Of the above is necessary to implement new behaviors or special procedures that provide solutions to eradicate the problem of violence within households, when they are misdemeanors and not when they take victims to regret, with which the emotional and in the economic possibly be for our system easier to solve, for the benefit of the people assaulted and their families.